The Human Factors Engineering Approach to Biomedical Informatics Projects: State of the Art, Results, Benefits and Challenges - Beuscart-Zéphir, M.-C.; Elkin, Peter; Pelayo, Sylvia; Beuscart, Regis (Yearbook of Medical Informatics, 2007)
The objective of this paper is to define a comprehensible overview of the Human Factors approach to biomedical informatics applications for healthcare. The overview starts with a presentation of the necessity of a proper management of Human factors for Healthcare IT projects to avoid unusable products and unsafe work situations. The first section is dedicated to definitions of the Human Factors Engineering (HFE) main concepts. The second section describes a functional model of an HFE lifecycle adapted for healthcare work situations. The third section provides an overview of existing HF and usability methods for healthcare products and presents a selection of interesting results. Thelast section discusses the benefits and limitations of the HF Eapproach.Literature review based on Pubmedand conference proceedings in the field of Medical Informatics coupled with a review of other databases and conference proceedings in the field of Ergonomics focused on papers addressing healthcare work and system design.Usability studies performed on healthcare applications have uncovered unacceptable usability flaws that make the systems error prone, thus endangering the patient safety. Moreover, in many cases, the procurement and the implementation process simply forget about human factors: following only technological considerations, they issue potentially dangerous and always unpleasant work situations. But when properly applied to IT projects, the HFE approach proves efficient when seeking to improve patient safety, users’ satisfaction and adoption of the products.We recommend that the HFE methodology should be applied to most informatics and systems development projects, and the usability of the products should be systematically checked before permitting their release and implementation. This requires the development of Centers specialized in Human Factors for Healthcare and Patient safety in each Country/Region.
Keywords: Human Factors Engineering; usability; socio-technical approach; healthcare IT applications; computer-controlled medical devices; patient safety; IT